Arquiteturas íntimas de Gê Orthof - Nery, Roseli Aparecida da Silva (2017)
Gê Orthof discusses in his work the behavior of the public in art exhibitions and the strength of the object as an activator of perception. The artist uses small objects that compose the space of the gallery in installations that suggest the deceleration of time, the immersion of the spectator and foments the debate about the potency of things as an invitation to the approach and the intimacy. His creative process is based on literature and personal experiences which results in a fertile topic of reflection in today’s art